POLITICAL CULTURE OF MANAGEMENT PERSONNEL IN NEW UZBEKISTAN STRATEGY (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
Practical work on improving educational sectors in our country, developing the field of competitive, qualified qualifications has created the necessary frameworks for a person's moral, spiritual, and educational perfection and harmonious development in all aspects. This is the basis for the rise of the political, social, economic, moral and cultural potential of personnel and the effective reforms undertaken in all sectors.